2017
DOI: 10.1186/s12913-017-2710-5
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of medical revalidation: an assessment using normalisation process theory

Abstract: BackgroundMedical revalidation is the process by which all licensed doctors are legally required to demonstrate that they are up to date and fit to practise in order to maintain their licence. Revalidation was introduced in the United Kingdom (UK) in 2012, constituting significant change in the regulation of doctors. The governing body, the General Medical Council (GMC), envisages that revalidation will improve patient care and safety. This potential however is, in part, dependent upon how successfully revalid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 19 publications
0
50
0
Order By: Relevance
“…In Table 2 , we show that NPT was employed in in 82 uncontrolled studies, and these generated 90/130 (69.2%) articles [ 59 – 148 ]. These included feasibility studies ( n = 20) and process evaluations ( n = 54), and seven were what we have called ‘field studies’ which focused on general conditions in which interventions might take place, rather than the progress of specific interventions.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 , we show that NPT was employed in in 82 uncontrolled studies, and these generated 90/130 (69.2%) articles [ 59 – 148 ]. These included feasibility studies ( n = 20) and process evaluations ( n = 54), and seven were what we have called ‘field studies’ which focused on general conditions in which interventions might take place, rather than the progress of specific interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Among the articles in this review exploring NPT use in UK primary care settings, none used NPT to explore the entire implementation course of an intervention. However, this is not uncommon; May et al [21] in their recent review identified only one longitudinal study [62].…”
Section: Key Findings Of This Reviewmentioning
confidence: 99%
“…As a middle range theory, NPT has been increasingly applied to many different healthcare specialities and contexts, including mental health [ 13 ], allied health [ 14 ], acute healthcare [ 15 ], primary healthcare settings [ 16 , 17 ] and medical revalidation [ 18 ] as an explanatory model to guide the development and implementation of complex interventions. We chose the NPT as an explanatory model to explore and evaluate the implementation of a complex intervention in the Operating Room (OR) context.…”
Section: Introductionmentioning
confidence: 99%